Evaluative study at Traffic & Road Safety Section in Police Command of Dili Municipality, Timor-Leste - Carlito Laku Tiris Mauloe (CV. Ulil Albab Corp, 2024)
The title of this scientific journal is “Public service ethic in traffic and road safety”, which is conducted evaluative study at PNTL Headquarter of Dili Municipality. The objective of this article is “to know how the application of public service ethic of bureaucrats or the traffic members of Timor-Leste National Police (TLNP) at the Traffic and road safety office, at Police Command of Dili municipality. The descriptive qualitative method had been applied in order to respond to the problem in this scientific journal. The data has been collected from primary and secondary data source, it’s obtained through interview with customer and the member of traffic police, observation of researcher and the relevant document. The result of this article indicated that nowadays, public service ethic towards traffic enforcement at the traffic and road safety office in Dili municipality Police command which seen from the legality, Moral, Administrative and work ethic approach are still less or not yet reach the maximum standard. Although, the aspect of abuse of authority has begun to disappear and the members had have capability to conduct the service. Required to Government through TLNP command to continue conducted maximum control to improve the public service ethic in traffic enforcement and road safety, continues to empower the members and apply the disciplinary regulations towards the members who violate the law and regulation when conducting public service.